METHODS OF USING LEXICAL LENDINGS - Ishankulova, Diyora (Журнал иностранных языков и лингвистики, 2023)
Our article looks at methods of using lexical fields. Vocabulary is known to be the most open subsystem of language. There is not a single language on this planet whose words are not borrowed from other languages. Borrowing is an integral part of the functioning and historical transformation of the language and one of the main sources of vocabulary filling.